How much time and who will do it? Organizing the toolbox of climate adaptations for small-scale fisheries - Bossier, Sieme; Ota, Yoshitaka; Pozas-Franco, Ana Lucía; Cisneros-Montemayor, Andrés M. (Frontiers in Marine Science, 2025)
Adaptation to climate impacts will be necessary for small-scale fisheries and fishers (SSFs) to safeguard their food security, livelihoods, and cultural heritage. SSFs are often vulnerable to environmental impacts due to the place-based, multi-scale and direct dependencies on local ecosystems, and generally fewer resources or abilities for relocation, diversification, and modification of their fishing practices. Strategic adaptation is therefore essential. This study emphasizes the timelines, requirements, and burdens of implementing existing and proposed adaptations, e.g., who pays, who does the work, and how long would it take? To categorize possible actions (tools) for analysis, we adapt the FAO climate adaptation framework and propose five areas of action: Institutional, Communication, Livelihood, Risk Resilience, and Science. Our results highlight two interconnected trends; first, the burdens and benefits of proposed climate adaptations are unevenly distributed, usually against fishers themselves. Second, there is a general lack of research focusing on the equity implications of current governance structures that de-emphasize fisher’s needs. This creates a lack of understanding among policy makers about the adaptation priorities of SSFs, and what resources or support they would need to implement them. We applied this framework to a case study involving octopus SSFs in Yucatán, Mexico. Interview results reinforce the finding that adaptation strategies that fishers thought would be most important for them (e.g. changes in policies/regulations to improve healthcare, reduce excess capacity, or reinforce fishing laws) were actions they could not often realize without external support; conversely, tools often proposed as “easier” by non-fishers (e.g. changing jobs, fishing gears, or going further out to sea) were not seen as particularly viable to fishers. Due to these mismatches, we argue there is a need to go beyond the classical focus on quantifying climate vulnerability towards a stronger emphasis on prioritizing adaptation strategies to meet the goals of fisherfolk themselves and aligning organizational and governance structures accordingly. The toolbox organization framework we propose can serve as an initial guidance for many fishing communities, decision makers and other stakeholders to anticipate implementation needs and find the right tools to adapt to future climatic conditions and prevent negative socioeconomic and ecological impacts.